Romania : Ex Post Evaluation of Exceptional Access Under the 2011 Stand-By Arrangement. - International Monetary Fund. Fiscal Affairs Dept. (Washington, D.C. : International Monetary Fund, 2014)
This 2004 Article IV Consultation on Romania highlights commendable progress under its home-grown IMF-supported program. Economic activity is picking up after a four-year slump, inflation remains low, the financial sector is stable, and the fiscal and external positions are improving. The 2014 budget aims to protect the gains under the program, continue the downward debt-to-GDP trajectory, and advance the reform agenda. Debt has fallen considerably owing to completion of a large part of the debt-land swap, but remains high. The authorities have taken welcome steps to strengthen the nonbank financial institutions supervisory framework.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet